3-Dimensional CFD simulation and experimental analysis on performance of a new diffuser and wind channel for a micro wind turbine - Darvishi, Zeinab; Najafi, Gholamhassan; Ghobadian, Barat; Nor Azwadi, Che Sidik; Rizalman, Mamat; Mohd Fairusham, Ghazali; Hoseini, Seyed Salar (Penerbit Akademia Baru, 2022)
Producing electricity from waste energies has been introduced as a useful approach in moving towards stability. Therefore, in the current study a new wind channel has been designed and fabricated to convert created airflow resulting from automobiles movement on the highways to electricity. This channel is fabricated to guide airflow from automobiles movement inside the same directed channel and towards a microturbine located at the bottom of the wind channel. To uniform the airflow inside the channel, a new diffuser has been designed and fabricated. The diffuser minimizes airflow turbulence in a part of the channel where microturbine is located. The maximum velocity is obtained in the horizontal distance is 1.9 m, the vertical distance is 0.95 m, and the angle is 45° according to automobiles' movement. This study also studied fluid behavior through the channel using 3-Dimensional CFD simulation technique and the best type of channel and diffuser fabricated based on numerical results. According to the numerical simulation results, the velocity of wind in channel venturi is 3.9 times more than the channel entrance velocity. As a result of numerical analysis and experimental investigation, by using the new diffuser and the new fabricated wind channel, the wind velocity between blades of the microturbine is 4.5 times more than the inlet velocity of the wind channel.